Post-traumatic posterior heel soft tissue defect reconstruction - M P Suri; A G Patel; H J Vora; S C Raibagkar; D R Mehta; U H Vyas (Indian Journal of Plastic Surgery)
We present a simple algorithm for management of post-traumatic posterior heel defect. We covered these with various flaps depending upon the defect size, its exact location, associated injuries, extent of zone of trauma, and complexity of the defect. The aim was to select the most suitable method for soft tissue coverage for posterior heel reconstruction.